European football after COVID-19 - Reade, J.; Singleton, C. (A new world post COVID-19: lessons for business, the finance industry and policy makers, 2020)
The European football industry has suffered an unprecedented shock from COVID-19. In this chapter, we reflect on how the sport`s administrators responded to the initial outbreaks and what lessons can be learned. We also look ahead to what football in the post-COVID-19 era could look like. We conclude that this largely depends on the decisions now facing the sport`s administrators and the powerful owners of the biggest football clubs: will they prioritise football as the inclusive and diverse game, at the heart of local communities? Or will their intrinsic financial interests dominate?